Simple mucin-type carbohydrate antigens (T, sialosyl T, Tn and sialosyl-Tn) in breast carcinogenesis - Schmitt, F. C. [UNESP]; Figueiredo, P. [UNESP]; Lacerda, M. [UNESP] (Springer Nature, 1995)
Immunohistochemical analysis of the expression of simple mucin-type carbohydrate antigens (Tn, sialyl-Tn and T) was performed in a series of 43 cases of intraductal hyperplasia without atypia, 9 cases of intraductal hyperplasia with atypia, 54 cases of ductal carcinoma in situ (DCIS) and 26 cases of invasive breast carcinoma. We also studied 36 cases of isolated breast normal epithelium, 20 cases of 'normal' breast epithelium adjacent to neoplasms and 14 cases of apocrine metaplasia. All antigens were detected in different frequencies in normal, hyperplastic, metaplastic and neoplastic breast epithelium. Tn and sialyl-Tn are expressed more frequently in malignant than in benign breast epithelium; while Tn expression increases from normal to invasive carcinomas, sialyl-Tn increases until DCIS and drops in invasive carcinomas, suggesting that either there is a failure of a proportion of DCIS to progress to invasive carcinoma or loss of expression of sialyl-Tn when some carcinomas become invasive. The high frequency of Tn and sialyl-Tn expression in breast intraductal proliferations probably reflects incomplete glycosylation in these lesions, which is a well-known tumour-associated phenomenon and supports the assumption that such lesions are putative precursors of breast cancer. T antigen was expressed in all groups studied, but its prevalence differed significantly between normal and neoplastic epithelium. The expression of these antigens in epithelium adjacent to carcinomas is similar to that found in isolated normal breast epithelium, whereas apocrine metaplasia has a pattern of simple mucin-type glycosylation that is specific and distinct from that of the normal breast epithelium, with a high frequency of marked expression of Tn and sialyl-Tn. The similarity of the pattern of expression of simple mucin-type antigens in metaplasia and malignant neoplasia reduces the usefulness of these markers from a diagnostic standpoint.
Keywords: Apocrine metaplasia; Breast carcinoma; Carbohydrate antigens; Hyperplasias; carbohydrate antigen; mucin like carcinoma associated antigen; apocrine gland; breast carcinogenesis; breast epithelium; cell proliferation; controlled study; disease course; female; glycosylation; human; human tissue; hyperplasia; immunohistochemistry; intraductal carcinoma; invasive carcinoma; major clinical study; metaplasia; priority journal; Antibodies, Monoclonal; Antigens, Surface; Antigens, Tumor-Associated, Carbohydrate; Breast; Breast Neoplasms; Carcinoma in Situ; Carcinoma, Infiltrating Duct; Female; Human; Hyperplasia; Immunohistochemistry; Metaplasia; Mucins; Neoplasm Invasiveness; Support, Non-U.S. Gov't; Tumor Markers, Biological